The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1016/j.chemosphere.2006.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Al-, Fe- and Mn-pools and their correlation in soils from two acid deposition small catchments in Hunan, China

Abstract: Distribution of Al-, Fe-and Mn-pools was investigated in five forest soil profiles (consisting of four horizons) in each of two Hunan catchments (BLT and LKS) where acid deposition has been considered critical. Al-and Fe-pools were higher in BLT than those in LKS, but Mn-pools much lower in BLT. Mn-pools vary from topsoils to bottom soils, but there are different trends for different Mn speciation. Al-and Fe-pools, except amorphous Fe ox , were positively correlated to contents of soil organic matter (OM) show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…2006; Zhou et al. 2003), we can safely conclude that Ex‐Fe is the most direct source of available Fe in soils, which is in agreement with other findings (Agbenin 2003; Xue et al. 2006; Young et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…2006; Zhou et al. 2003), we can safely conclude that Ex‐Fe is the most direct source of available Fe in soils, which is in agreement with other findings (Agbenin 2003; Xue et al. 2006; Young et al.…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that Ex‐Fe was positively related to DTPA‐Fe concentration at P < 0.01. In view of the fact that Ex‐Fe is the most available Fe in soils for plant absorption (Agbenin 2003; Xue et al. 2006; Young et al.…”
Section: Discussionmentioning
confidence: 99%
“…This theory is confirmed by results of research conducted by Kobierski (2004), where the highest amounts of Mn and Fe forms extracted with DTPA were determined in topsoils. Xue et al (2006) point to the existence of a relationship between Fe and the OM content, while at the same time stressing the possibility that this phenomenon may be intensified as a result of OM accumulation in soil. The cited authors do not, however, point to a connection between OM and Mn ions.…”
Section: Introductionmentioning
confidence: 82%
“…These elements are used by plants in small amounts (Walna et al, 2010). In the soil environment, Mn and Fe form numerous compounds and their bioavailability is conditioned by soil properties, mainly by the redox potential and pH (Xue et al, 2006). According to Livens (1991), Mn and Fe, which can be found in topsoils, can form complex bonds with OM and remain available for plants in this form.…”
Section: Introductionmentioning
confidence: 99%
“…To date, an increasing number of studies (Kelderman and Osman, 2007;Xue et al, 2006) have focused on heavy metal fractions in sediments, which should provide more information about environmental impacts on bioavailability. However, in these investigations, the hydrodynamic conditions were not adequately taken into consideration.…”
Section: Introductionmentioning
confidence: 99%